Topokaryotyping – a proposal for a novel approach to study nuclear organization - Jurisic, A.; Robin, C.; Ogryzko, V. (2015)
Gene positioning in the nucleus plays an important role in gene activity and genome stability, both in norm and pathology. We propose a new principle for the analysis of the large scale chromatin organization at the single-cell level, termed Topokaryotyping. It is based on coexpression in cells of (i) biotin ligase BirA targeted to a particular intranuclear domain (via its fusion with a protein-marker of this domain) together with (ii) BAP-histone fusion. The application of biotin pulse chase followed by (i) generation of mitotic spreads, (ii) detection of the biotin label and (iii) karyotyping technique to identify the chromosomes should provide information on the association of particular chromosome regions with the nuclear domain under study. We discuss potential advantages of the proposed approach as compared to other methods to study genome topology in the nucleus.